A Cognitive-Radio-Based Method for Improving Availability in Body Sensor Networks. (21st October 2015) - León, Olga; Hernández-Serrano, Juan; Garrigues, Carles; Rifà-Pous, Helena
Abstract : One of the main threats to body sensor networks (BSNs) is Denial of Service attacks that disrupt communications used to transmit patients' health data. The application of cognitive radio (CR) technology into BSNs can mitigate such a threat and improve network availability, by allowing network nodes to cooperatively agree on a new radio channel whenever the quality of the channel being in use decreases. However, the cooperative spectrum sensing mechanisms used by CRs should also be protected to prevent an attacker from predicting the new channel of operation. In this work, we present a lightweight and robust mechanism that appropriately secures the channel selection process while minimizing resources consumption, thus being suited for resource constrained devices such as body sensor nodes. The proposed method has been analyzed in terms of energy consumption and transmission overhead and it has been shown that it outperforms existing cryptographic approaches.